Eugenio Viola, el arte y las mujeres poderosas (REVISTA NODO, 2023)
Professional profile of the curator Eugenio Viola (Naples, 1975), current curator of the Museum of Modern Art of Bogotá (MamBo), prepared by the Mexican art historian Emilia Raggi.